2020
DOI: 10.1007/s11673-020-10002-1
|View full text |Cite
|
Sign up to set email alerts
|

Gambling with COVID-19 Makes More Sense: Ethical and Practical Challenges in COVID-19 Responses in Communalistic Resource-Limited Africa

Abstract: Informed by evidence from past studies and experiences with epidemics, an intervention combining quarantine, lockdowns, curfews, social distancing, and washing of hands has been adopted as "international best practice" in COVID-19 response. With massive total lockdowns complemented by electronic surveillance, China successfully controlled the pandemic in country within a few months. But would this work for Africa and other communalistic resource-poor settings where social togetherness translates to effective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…These findings are in line with Tirado and Schmidt (2000) who found that crucial food handling knowledge is on the decline among college students, as 45.6% of food borne illnesses are due to temperature abuses during food processing, poor refrigeration, and inappropriate storage temperatures of leftover or recently cooked meals. Comparable results were reported by Yusofetal (2018) and Nderitu et al (2020), as dietetics students in Malaysia only managed to only score (37.7%) in relation to the adequate temperature for reheating leftover food. Another study by Al-Shabib et al (2016) reported that only 50% of students in a Saudi Arabian university removed watches, rings, and jewelry before cooking.…”
Section: Discussionsupporting
confidence: 52%
“…These findings are in line with Tirado and Schmidt (2000) who found that crucial food handling knowledge is on the decline among college students, as 45.6% of food borne illnesses are due to temperature abuses during food processing, poor refrigeration, and inappropriate storage temperatures of leftover or recently cooked meals. Comparable results were reported by Yusofetal (2018) and Nderitu et al (2020), as dietetics students in Malaysia only managed to only score (37.7%) in relation to the adequate temperature for reheating leftover food. Another study by Al-Shabib et al (2016) reported that only 50% of students in a Saudi Arabian university removed watches, rings, and jewelry before cooking.…”
Section: Discussionsupporting
confidence: 52%
“…Hagan et al emphasized the need for public health infrastructure development (e.g., laboratories, infectious disease centres, regional hospitals), human capacity building, and regular public health educational campaigns for combating COVID and potential future outbreaks [ 6 ]. Other barriers to response efforts include lack of availability of water sanitation and hygiene (WASH) services in health facilities [ 18 ], challenges to re-organisation of care delivery [ 19 ] and practical challenges such as social distancing and quarantine in the economic and social context of Africa [ 20 ]. While lockdown measures designed to control the prevalence, interrupted health services access and caused social and economic disruption [ 21 ].…”
Section: Introductionmentioning
confidence: 99%